2008
DOI: 10.3354/meps07614
|View full text |Cite
|
Sign up to set email alerts
|

Male reproductive success during spawning events of the octocoral Pseudopterogorgia elisabethae

Abstract: Many sessile organisms rely on the transport of one or both types of gametes for reproductive success. While sperm limitation has been reported in some species, high fertilization success has been observed in others including the branching octocoral Pseudopterogorgia elisabethae. In such cases, males may compete for eggs to fertilize and the local dispersion of sperm will be an important component of male success. Individual reproductive success of 91 male P. elisabethae colonies found within a 400 m 2 area on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
1
23
1
Order By: Relevance
“…Mean sperm dispersal of 5.5 m is similar to estimates for a surface egg‐brooding gorgonian (5.2 m; Lasker et al . ), although the maximum distance found here (17 m) is 50% greater. Estimates of sperm dispersal for other spermcasting marine invertebrates (Grosberg , ; Yund ; Pemberton et al .…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Mean sperm dispersal of 5.5 m is similar to estimates for a surface egg‐brooding gorgonian (5.2 m; Lasker et al . ), although the maximum distance found here (17 m) is 50% greater. Estimates of sperm dispersal for other spermcasting marine invertebrates (Grosberg , ; Yund ; Pemberton et al .…”
Section: Discussioncontrasting
confidence: 63%
“…In a paternity analysis of the brooding gorgonian Pseudopterogorgia elisabethae , mean sperm dispersal was 5.2 m (±3.1 SD; max = 11.8 m) under similar adult densities and reef area to this study (Lasker et al . ). Given the density of the population studied here (0.5/m), where the mean distance between maternal colonies and potential sires was 7.32 m (±4.56 SD; max = 22.42 m), the assumption of 90% of potential fathers sampled seems reasonable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Two studies examining multiple paternity in spermcasting marine invertebrates found that some offspring were fathered by individuals outside the study area (Yund , 300 m 2 ; Lasker et al . , 400 m 2 ). In two spermcasters, a gorgonian and a sponge, reproductive success was not correlated with proximity to mates, suggesting distance may not limit fertilization (Lasker et al .…”
Section: Discussionmentioning
confidence: 99%
“…In two spermcasters, a gorgonian and a sponge, reproductive success was not correlated with proximity to mates, suggesting distance may not limit fertilization (Lasker et al . , 400 m 2 ; Maritz et al . , 50 m 2 ).…”
Section: Discussionmentioning
confidence: 99%